Pengaruh Implementasi Program “Temanku Sahabatku” dalam Meningkatkan Perilaku Prososial Anak Pra Sekolah - Restuwati, Evi Sri; Kumara, Amitya (HUMANITAS, 2014)
ABSTRACTProsocial behavior made unique contributions to the prediction of educational achievement, sociability in the early years. Prosocial behavior was defined as acting that is either beneficial to or intended to benefit other people. Prosocial behavior could be expressed as helping, supporting, physical affection, or sharing. The “Temanku Sahabatku” program was adopted from a large themesfrom the book of The Anti-Bullying and Teasing Program for Preschool by Sprung, et al (2005), friendship theme. The “Temanku Sahabatku” program was the program which was designed as an effort to avoid bullying at school by improved children prosocial behavior. Teachers and students of two preschools in Sleman was going to involve in this study. This study was going to use quasiexperiment design, the untreated control group design with pre-test and post-test. Teachers were asked to implement the program which was trained before into first year preschoolers classroom in experiment group. The result of this study was the implementation of “Temanku Sahabatku” program was effective to improve the prosocial behavior of preschool children in experiment group rather than control group (F=26,506; MD= -2,200; p<0,05).Keywords: Program Anti-Bullying, friendship theme, prosocial behavior.